Modulation of TLR3/TLR4 inflammatory signaling by the GABAB receptor agonist baclofen in glia and immune cells: relevance to therapeutic effects in multiple sclerosis - Crowley, Tadhg; Fitzpatrick, John-Mark; Kuijper, Teun; Cryan, John F.; O’Toole, Orna; O’Leary, Olivia F.; Downer, Eric J. (Frontiers in Cellular Neuroscience, 2015)
The GABAB receptor agonist, baclofen, is used to treat muscle tightness and cramping caused by spasticity in a number of disorders including Multiple Sclerosis (MS), but its precise mechanism of action is unknown. Neuroinflammation drives the central pathology in MS and is mediated by both immunoreactive glial cells and invading lymphocytes. Furthermore, a body of data indicates that the Toll-like receptor (TLR) family of innate immune receptors is implicated in MS progression. In the present study we investigated whether modulation of GABAB receptors using baclofen can exert anti-inflammatory effects by targeting TLR3 and(or) TLR4-induced inflammatory signaling in murine glial cells and human peripheral blood mononuclear cells (PBMCs) isolated from healthy control individuals and patients with the relapse-remitting (RR) form of MS. TLR3 and TLR4 stimulation promoted the nuclear sequestration of NF-κB and pro-inflammatory cytokine expression in murine glia, while TLR4, but not TLR3, promoted pro-inflammatory cytokine expression in PBMCs isolated from both healthy donors and RR-MS patients. Importantly, this effect was exacerbated in RR-MS patient immune cells. We present further evidence that baclofen dose-dependently attenuated TLR3- and TLR4-induced inflammatory signaling in primary glial cells. Pre-exposure of PBMCs isolated from healthy donors to baclofen attenuated TLR4-induced TNF-α expression, but did not affect TLR4-induced TNF-α expression in RR-MS patient PBMCs. Interestingly, mRNA expression of the GABAB receptor was reduced in PBMCs from RR-MS donors when compared to healthy controls, an effect that might contribute to the differential sensitivity to baclofen seen in healthy and RR-MS patient cells. Overall these findings indicate that baclofen differentially regulates TLR3 and TLR4 signaling in glia and immune cells, and offers insight on the role of baclofen in the treatment of neuroinflammatory disease states including MS.